Радиационно стойкая фотоструктура на основе Cr/In₂Hg₃Te₆ для диода Шоттки - Ащеулов, А.А.; Галочкин, А.В.; Романюк, И.С.; Дремлюженко, С.Г. (Технология и конструирование в электронной аппаратуре, 2016)
Представлены конструкция и технология изготовления структуры фотодиода Шоттки на основе подложки из радиационно-стойкого кристалла n-In₂Hg₃Te₆ с барьерным слоем из Cr, характеризуемого фотоответом в области 0,6—1,6 мкм при максимальной чувствительности 0,43 А/Вт на длине волны 1,55 мкм. Исследования электрических параметров этих фотодиодных структур показали, что высота потенциального барьера составляет 0,41 эВ, а величина обратного темнового тока не превышает 4 мкА. Созданные устройства сохраняют свою работоспособность при дозах гамма-облучения 2x10⁸ бэр. Представлено конструкцію і технологію виготовлення структури фотодіода Шотткі на основі підкладки з радіаційно стійкого кристала n-/In₂Hg₃Te₆ з бар'єрним шаром з Cr, що характеризується фотовідповіддю в області 0,6—1,6 мкм при максимальній чутливості 0,43 А/Вт на довжині хвилі 1,55 мкм. Дослідження електричних параметрів цих фотодіодних структур показали, що висота потенційного бар'єру складає 0,41 еВ, а величина зворотного темнового струму не перевищує 4 мкА. Створені пристрої зберігають свою працездатність при дозах гама-опромінення 2x10⁸ бер. Schottky photodiode structure was designed on the base of this semiconductor formed by a modified floating zone recrystallization technique where the sedimentation effect was leveled. It consists of n-In₂Hg₃Te₆ substrate and deposited by cathode sputtering Cr barrier layer of thickness within a range 10-11 nm choice of Cr is determined by its optimal optical, electric and adhesive features in high quality radiation-resistant photodiode structures manufacturing. Indium and nichrome are used as ohmic contacts. The barrier structures have the contact area of 1,13 mm² with photo response of 0,6-1,6 mm at the maximal sensitivity 0,43 A/W on the wavelength l,55 mm. Reverse dark current of these structures do not exceed 4 mA at the bias of 1 V (T=295 K), and the potential barrier height is equal to 0,41 eV. The tests of radiation resistance of these structures demonstrated their ability to function at doses of 2x10⁸ rem without evident parameters changes. This allows using them in practical aims in the conditions of high radiation.